ANALISIS WACANA IKLAN ROKOK SAMPOERNA MILD - Puspita Dewi; Sulmi Magfirah (Humanitatis : Journal of Language and Literature, 2018)
Mass media is one of the great services utilized by people who have the purpose of selling goods and providing services to the public. Mass media is the right market to promote an item or service so that choosing the right diction is a must. The purpose of this study is to identify the meaning of the sentence in the Sampoerna Mild cigarette advertisement "nggak ada Loe, nggak Rame". The research method used is descriptive qualitative using an approach that are hermeneutic and semiotic. The results of the study show that the choice of words in the advertisement has a very persuasive and interesting meaning which has very close social relations. The meaning of " nggak ada Loe, nggak Rame" is a good diction for teenagers who are quickly affected to their peers. This is because teenagers are more likely to like to hang out with their teenage friends. Language, culture and society have strong and good connection.